PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DAN MINAT BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU DI SMP NEGERI 2 TANTOM ANGKOLA - Eli Santana Siregar; Sri Ulfa Sentosa (Jurnal Kajian Pendidikan Ekonomi, 2015)
The results of research revea:l (1) learning outcomes social class integrated use the model of learning cooperative type make a match higher than in learning outcomes that were taught by a method varied talk. (2) learning outcomes integrated social class students who have learning high interest that were taught by using cooperative kind of classroom type make a match higher than learning outcomes students who have learning high interest be taught with the methods varied talk. (3) learning outcomes integrated social class students who have learning low interest that were taught with cooperative kind of classroom type make a match higher learning outcomes integrated social class students who have learning low interest that were taught by a method varied talk. (4) there was no interaction between cooperative kind of classroom type make a match with their respective interest learn student learning of the results on the subjects of integrated social class, it means a model make a match accepted for all students. Keyword : cooperative learning type make a match, a method varied talk, learning interest